An automated calculation pipeline for differential pair interaction energies with molecular force fields using the Tinker Molecular Modeling Package - Bänsch, Felix; Daniel, Mirco; Lanig, Harald; Steinbeck, Christoph; Zielesny, Achim (Journal of Cheminformatics, 2024)
An automated pipeline for comprehensive calculation of intermolecular interaction energies based on molecular force-fields using the Tinker molecular modelling package is presented. Starting with non-optimized chemically intuitive monomer structures, the pipeline allows the approximation of global minimum energy monomers and dimers, configuration sampling for various monomer–monomer distances, estimation of coordination numbers by molecular dynamics simulations, and the evaluation of differential pair interaction energies. The latter are used to derive Flory–Huggins parameters and isotropic particle–particle repulsions for Dissipative Particle Dynamics (DPD). The computational results for force fields MM3, MMFF94, OPLS-AA and AMOEBA09 are analyzed with Density Functional Theory (DFT) calculations and DPD simulations for a mixture of the non-ionic polyoxyethylene alkyl ether surfactant C10E4 with water to demonstrate the usefulness of the approach. Scientific Contribution To our knowledge, there is currently no open computational pipeline for differential pair interaction energies at all. This work aims to contribute an (at least academically available, open) approach based on molecular force fields that provides a robust and efficient computational scheme for their automated calculation for small to medium-sized (organic) molecular dimers. The usefulness of the proposed new calculation scheme is demonstrated for the generation of mesoscopic particles with their mutual repulsive interactions.
CRIS-Team Scopus Importer:2024-08-16
Keywords: C; Dimer; Dissipative particle dynamics; DPD; Flory–Huggins parameter; Intermolecular interaction; Isotropic repulsion; Molecular dynamics; Molecular force field; Molecular modeling; Monomer; Non-ionic polyoxyethylene alkyl ether surfactant; Nonbonding interaction